Evaluasi Pembelajaran Bahasa Inggris pada Sekolah Menengah Kejuruan - Harjali, Harjali (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2012)
Instructional evaluation cannot be separated from the effort of classroom based assessment done by teachers. Teachers are expected to have sufficient competency to do the evaluation so that it can provide information of the actual data of their student’s competency. Foreign language instructional process in vocational school is one of the competencies which is required to be optimally achieved because students are expected to apply it directly in their job later. Therefore, teachers play an important role to do instructional activity and particularly in terms of evaluation. This article aims at describing English teachers’ competence in SMK PGRI 2 Ponorogo, by analyzing deeply: instructional evaluation activity, English teacher’s evaluation competence, and also the efforts to improve English teachers’ competence in that school. Assessment activities done based on the educational assessment standard determined by government regulation and they are technically done in accordance with competence based assessment principles. Assessment activities have been done in various techniques. They are test and non test in order to assess both cognitive and psychomotor aspects. In fact, affective aspect has not been assessed yet. In general, In relation to English teachers’ competence, SMK PGRI 2 Ponorogo has done the instructional evaluation well through classroom based assessment. There are three competence aspects which are investigated; they are competence to prepare the evaluation, to implement the evaluation, and to report the evaluation. From those three aspects, the first aspect which is dealing with preparation still needs to be improved. Efforts to improve the evaluation are continuously done by teachers both individually and institutionally supported by the school. It is done by teachers individually through their participations to join several seminars and workshops both in local and also national level. The school supports them by setting the agenda and implements it by sending the teachers to seminars and trainings outside the school, to have socialization which are dealing with evaluation and assessment activity, and to provide technology based infrastructures.